In memoriams of Professor Zbigniew Życzkowski (1910-1988), Professor Wiktor Jankowski (1905-1988), Doctor Jerzy Jaroszyński (1923-1989), Professor Stanisław Kossowski (1909-1989) - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1990)
No abstract.